The CLASS (Cerebral visual impairment Learning and Awareness for School Staff) Pilot Study: An evaluation of the awareness of CVI amongst teachers and comparative evaluation of two different educational resources on understanding - Aloka Jayasinghe; Helen St Clair Tracy; John Ravenscroft; Andrew Blaikie (PLoS ONE, 2025)
Cerebral visual impairment (CVI) is the leading cause of visual impairment in children in high income countries. Despite its prevalence, awareness of CVI among educators remains low, meaning that many affected children may not receive the support they need in school. While previous research has highlighted the challenges faced by children with CVI, few studies have systematically assessed teacher awareness and the effectiveness of targeted educational interventions in improving classroom practices. This study addresses this gap by evaluating: (1) teacher awareness of CVI, (2) existing classroom practices that may impact children with CVI, (3) the effectiveness of two CVI educational media formats (video and text) in increasing understanding, and (4) the changes teachers would be willing to implement following exposure to these resources. By comparing the impact of these two formats, this study provides insights into how best to deliver CVI training for teachers in a way that is both accessible and effective. A total of 111 teachers from primary, secondary, and special schools across the UK participated in a survey incorporating either a three-minute video simulation or a 1.5-minute text-based resource about CVI. Before exposure, 72% of participants had not heard of CVI, with awareness particularly low among mainstream teachers (98% of primary and 80% of secondary teachers were unaware). Teachers also reported inconsistent use of CVI-supportive practices, such as reducing classroom clutter and simplifying smart screen content. Both media formats significantly increased teachers’ willingness to implement changes (p < 0.0001). The text format showed a slightly greater increase in average Likert scores, and the Wilcoxon signed-rank test revealed a larger statistical effect for text (z = -12.91) compared to video (z = -8.90). However, the video format was also highly effective, producing a similarly strong impact, with both formats achieving an identical median increase of 1.0. These results suggest that while text may have led to slightly larger shifts in rank-based scores, the video format remained a powerful and engaging tool for increasing teachers’ willingness to implement CVI-supportive strategies. The findings suggest that small, manageable adaptations, such as reducing visual distractions and maintaining consistency in classroom layouts, are practical for teachers and may have a meaningful impact on children with CVI. This study highlights the potential of bite-size learning resources in raising awareness and encouraging evidence-based teaching adaptations. By providing concise, accessible materials, teachers can be equipped with strategies to support children with CVI while minimising additional workload demands. Future efforts should focus on scaling these resources to reach a wider audience, including families and caregivers, to foster a more inclusive understanding and response to CVI.